New records of the hypercalcified sponge Plectroninia (Calcarea, Minchinellidae) in the Recent deep ocean. Issue 2 (3rd April 2018) - Vacelet, Jean; James, Benjamin; Zibrowius, Helmut
Abstract : Vacelet, J., James, B. 1, &Zibrowius, H., November 2017. New records of the hypercalcified sponge Plectroninia (Calcarea, Minchinellidae) in the Recent deep ocean. Alcheringa 42, 312–319. ISSN 0311-5518 Numerous small specimens of hypercalcified sponges of the genus Plectroninia (Jurassic to Recent) are recorded from deep water in the Atlantic, Indian and Pacific oceans, where they are attached to diverse hard substrata, mostly scleractinian skeletons. Being represented as skeletons of linked calcareous tetractines with an incomplete free spicule complement, the specimens could not be identified at the species level. These observations show that Plectroninia spp. have a wide distribution in the bathyal zone of the Recent World Ocean, where they may be the most common calcareous sponges. Jean Vacelet* [ jean.vacelet@imbe.fr ], Benjamin James [ ben.james672@gmail.com ], Helmut Zibrowius [ helmut.zibrowius@gmail.com ] UMR 7263 IMBE, Institut Méditerranéen de Biodiversité et d'Écologie Marine et Continentale, CNRS, IRD, Aix Marseille Université, Avignon Université, Station Marine d'Endoume, Rue de la Batterie des Lions, 13007 Marseille, France.